(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
The purpose is to analyze the impact that armed conflict has had on school dropout rates in Colombia, given that women are the most affected by forced displacement. After the death of their partners, which is common in these cases, women are left with the responsibility of caring for the home and supporting their children. The problem of school dropouts in Colombian educational institutions has been treated as complex in certain cases, such as premature pregnancies, child labor, and lack of motivation to study, and defined according to urban or rural housing sectors. However, from a research perspective, the underlying cause is the displacement of Colombian families in different sectors.